The transmembrane region is responsible for targeting of adaptor protein LAX into "heavy rafts" - Hrdinka, Matous; Otahal, Pavel; Horejsi, Vaclav (PloS one, 2012)
BACKGROUND: The importance of membrane compartmentalization into specific membrane microdomains has been shown in many biological processes such as immunoreceptor signaling, membrane trafficking, pathogen infection, and tumor progression. Microdomains like lipid rafts, caveolae and tetraspanin enriched microdomains are relatively resistant to solubilization by some detergents. Large detergent-resistant membrane fragments (DRMs) resulting from such membrane solubilization can be conveniently isolated by density gradient ultracentrifugation or gel filtration. Recently, we described a novel type of raft-like membrane microdomains producing, upon detergent Brij98 solubilization, "heavy DRMs" and containing a number of functionally relevant proteins. Transmembrane adaptor protein LAX is a typical "heavy raft" protein. The present study was designed to identify the molecular determinants targeting LAX-derived constructs to heavy rafts. METHODOLOGY/PRINCIPAL FINDINGS: We prepared several constructs encoding chimeric proteins containing various informative segments of the LAX sequence and evaluated their effects on targeting to heavy rafts. Replacement of the polybasic membrane-proximal part of LAX by CD3ε-derived membrane-proximal part had no effect on LAX solubilization. Similarly, the membrane-proximal part of LAX, when introduced into non-raft protein CD25 did not change CD25 detergent solubility. These results indicated that membrane-proximal part of LAX is not important for LAX targeting to heavy rafts. On the other hand, the replacement of transmembrane part of CD25 by the transmembrane part of LAX resulted in targeting into heavy rafts. We also show that LAX is not S-acylated, thus palmitoylation is not involved in LAX targeting to heavy rafts. Also, covalent dimerization was excluded as a cause of targeting into heavy rafts. CONCLUSIONS/SIGNIFICANCE: We identified the transmembrane domain of LAX as a first motif targeting transmembrane protein constructs to detergent-resistant heavy rafts, a novel type of membrane microdomains containing a number of physiologically important proteins.
Keywords: adaptorové proteiny vezikulární transportní; membránové mikrodomény; buněčné linie; Adaptor Proteins, Vesicular Transport; Protein Interaction Domains and Motifs; Cell Line; multimerizace proteinu; lidé; interakční proteinové domény a motivy; Membrane Microdomains; Humans; Protein Multimerization